Changes in Notch signaling coordinates maintenance and differentiation of the Drosophila larval optic lobe neuroepithelia. - Weng, M.; Haenfler, J.M.; Lee, C.Y. (Developmental Neurobiology, 2012)
A dynamic balance between stem cell maintenance and differentiation paces generation of post-mitotic progeny during normal development and maintenance of homeostasis. Recent studies show that Notch plays a key role in regulating the identity of neuroepithelial stem cells, which generate terminally differentiated neurons that populate the adult optic lobe via the intermediate progenitor cell type called neuroblast. Thus, understanding how Notch controls neuroepithelial cell maintenance and neuroblast formation will provide critical insight into the intricate regulation of stem cell function during tissue morphogenesis. Here, we showed that a low level of Notch signaling functions to maintain the neuroepithelial cell identity by suppressing the expression of pointedP1 gene through the transcriptional repressor Anterior open. Increased Notch signaling, which coincides with transient cell cycle arrest but precedes the expression of PointedP1 in cells near the medial edge of neuroepithelia, defines transitioning neuroepithelial cells that are in the process of acquiring the neuroblast identity. Transient up-regulation of Notch signaling in transitioning neuroepithelial cells decreases their sensitivity to PointedP1 and prevents them from becoming converted into neuroblasts prematurely. Down-regulation of Notch signaling combined with a high level of PointedP1 trigger a synchronous conversion from transitioning neuroepithelial cells to immature neuroblasts at the medial edge of neuroepithelia. Thus, changes in Notch signaling orchestrate a dynamic balance between maintenance and conversion of neuroepithelial cells during optic lobe neurogenesis.